Model updating of nonlinear dynamic system using strong vibration data - Franciscus, Christiandy (2016)
Reliability updating in nonlinear dynamic system is essential in structural health monitoring and structural control because uncertainties exist in the evaluation of structural dynamic parameter values. These uncertainties are caused by many factors, such as material variability, inaccurate construction process, material deformation due to earthquake and material deterioration throughout the structure lifetime. Using wrong parameter values in assessing the structural dynamic response could lead to invalid structural reliability. Together with nonlinear hysteretic response behavior of the structure, these uncertainties cause the nonlinear system reliability updating problem to be complex.